THE IMPACT OF CELEBRITY ENDORSEMENT, ONLINE CUSTOMER REVIEWS, AND PURCHASE DECISIONS ON CONSUMER SATISFACTION IN GREATER SURABAYA’S BEAUTY INDUSTRY - Oksi Wijaya Kusuma Efendi; Rita Ambarwati Sukmono; Mas Oetarjo (PT ANTIS INTERNATIONAL PUBLISHER, 2025)
Objective: This study aims to analyze the influence of Celebrity Endorsement (CE), Online Customer Review (OCR), and Purchase Decision (KP) on Consumer Satisfaction (KK) in the beauty industry across the Greater Surabaya area. Method: A quantitative survey approach was employed by distributing online questionnaires to 100 respondents who are users of Scarlett Whitening products. Data were analyzed using SmartPLS 4.1, including validity, reliability, and structural model testing. Result: The results reveal that OCR and KP have a positive and significant effect on consumer satisfaction, while CE shows no significant impact. The model achieved an R² value of 0.818, indicating substantial predictive ability. Novelty: These findings suggest that online customer reviews and purchase decisions play a more crucial role in enhancing consumer satisfaction compared to celebrity endorsements. Practically, the study highlights the importance of managing online reviews and optimizing consumer experience to strengthen brand loyalty in the beauty industry.